Star Power Providing for the Gifted & Talented. Module 6. Underachievers Among the Gifted/Talented - Heinemann, Alison; Education Service Center Region 13, Austin, TX. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
The document presents Module 6, underachievers among the gifted/talented, of the Star Power modules developed for school personnel who have an interest in or a need to explore the area of gifted and talented education. It is explained in an introductory section that the modules can be used for independent study, for small group interaction, or for a large group inservice program. The goals of this module are to realize the extent and significance of underachievers among the gifted/talented and to discover ways to help gifted underachievers fulfill hidden potential. Sections include the following: enabling objectives (such as list at least eight different causes of underachievement among the gifted); rationale to establish a frame of reference; preassessment tests and evaluation; instructions for scoring the preassessment instrument; activities (which cover such topics as organizing a small group of underachievers for therapy sessions and administering the Structure of Intellect Learning Abilities Test to determine each underachievers strengths); and postassessment procedures. (SBH)
Availability: Education Service Center, Region XIII, 7703 North Lamar Boulevard, Austin, Texas 78752 ($78.00 per set; $6.00).
ERIC Note: Due to copyright restrictions the appendixes are not included in the series; Best Available Copy; For related information, see EC 120 594-604.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Secondary Education; Gifted; Inservice Education; Inservice Teacher Education; Program Guides; Resource Materials; Talent; Teacher Evaluation; Teacher Workshops; Tests; Underachievement; Gifted Handicapped; Guides, Non-Classroom.; Tests/Questionnaires.